Islamic Social Finance and Environmental Sustainability: A Study of Waqf-Driven Smart Waste Sorting and Recycling Solutions - Adamu Abubakar Muhammad; Shafa’at Ahmad Aliyu; Rabi Shehu Dalhatu; Huma Khan; Khadija Abdullahi (PT. Student Rihlah Indonesia, 2026)
Solid waste management problems are getting worse in Muslim-majority communities due to rapid urbanization, poor funding, and a lack of technological integration.AI developments offer promising answers for recycling and garbage sorting, but their use is hampered by expenses and a lack of assistance. The function of waqf, or Islamic endowments, as a sustainable financing option consistent with Islamic principles is examined in this paper. It seeks to evaluate current waqf-funded environmental projects, determine whether AI in trash management is compatible with Islamic beliefs, and suggest a structure for